High-Index Faceted Nanocrystals as Highly Efficient Bifunctional Electrocatalysts for High-Performance Lithium–Sulfur Batteries - Jiang, Bo; Tian, Da; Qiu, Yue; Song, Xueqin; Zhang, Yu; Sun, Xun; Huang, Huihuang; Zhao, Chenghao; Guo, Zhikun; Fan, Lishuang; Zhang, Naiqing (Nano-micro letters, 2022)
Highlights High-index faceted Fe 2 O 3 nanocrystals with abundant unsaturated Fe sites not only have strong adsorption capacity to anchor LiPSs but also have superior catalytic activity to facilitate the redox conversion of LiPSs and reduce the decomposition energy barrier of Li 2 S. Our work deepens the comprehending of facet-dependent activity of catalysts in Li–S chemistry and affords a novel perspective for the design of advanced sulfur electrodes. Precisely regulating of the surface structure of crystalline materials to improve their catalytic activity for lithium polysulfides is urgently needed for high-performance lithium–sulfur (Li–S) batteries. Herein, high-index faceted iron oxide (Fe 2 O 3 ) nanocrystals anchored on reduced graphene oxide are developed as highly efficient bifunctional electrocatalysts, effectively improving the electrochemical performance of Li–S batteries. The theoretical and experimental results all indicate that high-index Fe 2 O 3 crystal facets with abundant unsaturated coordinated Fe sites not only have strong adsorption capacity to anchor polysulfides but also have high catalytic activity to facilitate the redox transformation of polysulfides and reduce the decomposition energy barrier of Li 2 S. The Li–S batteries with these bifunctional electrocatalysts exhibit high initial capacity of 1521 mAh g −1 at 0.1 C and excellent cycling performance with a low capacity fading of 0.025% per cycle during 1600 cycles at 2 C. Even with a high sulfur loading of 9.41 mg cm −2 , a remarkable areal capacity of 7.61 mAh cm −2 was maintained after 85 cycles. This work provides a new strategy to improve the catalytic activity of nanocrystals through the crystal facet engineering, deepening the comprehending of facet-dependent activity of catalysts in Li–S chemistry, affording a novel perspective for the design of advanced sulfur electrodes.